Tissue vascularization through 3D printing: Will technology bring us flow?. Issue 5 (21st April 2015) - Paulsen, S.J.; Miller, J.S.
<x xml:space="preserve">Abstract</x> Background: Though in vivo models provide the most physiologically relevant environment for studying tissue function, in vitro studies provide researchers with explicit control over experimental conditions and the potential to develop high throughput testing methods. In recent years, advancements in developmental biology research and imaging techniques have significantly improved our understanding of the processes involved in vascular development. However, the task of recreating the complex, multi‐scale vasculature seen in in vivo systems remains elusive. Results: 3D bioprinting offers a potential method to generate controlled vascular networks with hierarchical structure approaching that of in vivo networks. Bioprinting is an interdisciplinary field that relies on advances in 3D printing technology along with advances in imaging and computational modeling, which allow researchers to monitor cellular function and to better understand cellular environment within the printed tissue. Conclusions: As bioprinting technologies improve with regards to resolution, printing speed, available materials, and automation, 3D printing could be used to generate highly controlled vascularized tissues in a high throughput manner for use in regenerative medicine and the development of in vitro tissue models for research in developmental biology and vascular diseases. Developmental Dynamics 244:629–640, 2015. © 2015 Wiley Periodicals, Inc.